Systematics and Phylogeny of Family Reduviidae Latreille, 1807 (Insecta: Hemiptera: Heteroptera) in Sarawak - Siti Hanisah, Zahuri (Universiti Malaysia Sarawak(UNIMAS), 2018)
The family Reduviidae Latreille, 1807 (Insecta:Hemiptera: Heteroptera) is composed approximately 25 subfamilies, 913 genera and with almost 7,000 species worldwide, their diversity was mostly found in the tropics. However, it is yet the most poorly studied species of Reduviidae. In Sarawak, there is no effort done on the systematics and phylogeny study on heteropterans although there were some revisions of genus and species that have been documented. The findings of this study will be useful as the fundamental to ecological and pest management of heteropterans and significantly contribute to the worldwide studies of Reduviidae. This study constructs a phylogenetic tree of described species of Reduviidae in Sarawak based on the morphological structures with reference to voucher specimens from UNIMAS Insect Reference Collection (UIRC), Forest Research Centre (FRC), Semongok Agriculture Research Centre (ARC), and Sarawak Biodiversity Centre (SBC), as well as new field collections. A phylogenetic analysis using maximum parsimony criteria which included 101 ingroup and 3 outgroup (Pentatomorpha) of taxa based on 61 morphological structures was run using Tree Analysis using New Technology (TNT) software is constructed. The monophyly of Reduviidae is well supported with Pentatomorpha as their outgroup. The results also present the monophyly of Tribelocephalinae, Salyavatinae, and Ectrichodiinae in a clade that also include Physoderinae, Saicinae and Reduviinae (Acanthaspis quadriannulata). The monophyly of Harpactorinae with basal position of Harpactorini in a clade is presented. In addition, a systematic account based on 23 genera and 52 species of subfamily Harpactorinae is presented. A key to the genera Harpactorinae is provided based on the comparative morphological structures with addition geological distribution map of each Harpactorinae species in Sarawak.